Analyzing temporal data for understanding the learning process induced by metacognitive prompts. (April 2021) - Engelmann, Katharina; Bannert, Maria
Highlights: Transfer performance is not necessarily facilitated by metacognitive prompts. Learners supported by metacognitive prompts express more strategical activities. Process models of self-regulation of supported and unsupported learners are similar. Sequences of SRL seem more important in explaining performance than frequencies.